Boko Haram Terror: A Historicism on Fighting for "god" for Spiritual Landing in Nigeria Under a Welcoming Government. (June, 2019 - April, 2020) - Anaele, Cyril (European Journal of Historical Research, 2021)
Following Buhari re - election in 2019, many wings of Boko Haram Islamist gangs emerged in the Nigeria's terrorist's scene. Whereas Boko Haram confined its killings in the N.E of Nigeria, these new brands of Boko Haram have national spread. The new killing columns of Boko Haram descendants are (i) the Islamic State of West African Province ISWAP, (ii) the Jama'atu Ansril Muslimina Naijeriya (aka Ansaru) (iii) the Fulani Herdsmen Jihadists and (iv) the High - ways "Bandits." Each gang has its mapped out target geo-political zone. Their shared mandate is Islamisation, and eradication of Christianity. But told, the earlier victims of Boko Haram were Christians and Muslims, but the specific target of the current upsurging and sweeping terror, generally, if not all, are Christians. Instead of addressing the killings, Buhari administration favours creating soft landing and welcoming "repentant" terrorists, through his Operation Safe Corridor and empowerment action policies for the Fulani herdsmen jihadists. The paper adopts Huntington's theory of clash of civilization and Healy's multi - casual theory. In methodology, it relied on qualitative technique, using secondary data. In presentation, it used historical method of unit data analysis. The major finding is that Nigeria is sitting on gun-power, anxiously waiting to spark off religious war, if the present administration continues to give Christian killer terrorists a friendly hand - shake. The paper recommends maximum punishment for terrorists and genuine commitment of Buhari to the preservation of Nigeria's secularity, if the pending religious war and/or retaliatory genocide against the Fulani killers of Nigerians is to be prevented from implosion.